Penerapan Model Problem Based Learning Untuk Meningkatkan Hasil Belajar Pendidikan Pancasila Siswa Kelas IV B SDN Pakis 1 Surabaya - Nurul Fadilah Hidayati; Bekti Wirawati; Nunuk Suliyastuti (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This study is an action research aimed at improving the learning outcomes of Pancasila Education on the topic of Appreciating Differences in Community Identity for Grade IV B students at SDN Pakis 01 Surabaya, which comprises 24 students. The research employs data collection methods such as observation, testing, and documentation. The instructional approach utilized is Problem-Based Learning (PBL). Findings indicate that the Problem-Based Learning model significantly improves students' Pancasila Education performance. Specifically, pre-cycle results showed a completion rate of 27%, which increased to 46% in Cycle I, and further rose to 81% in Cycle II. The implementation of Problem-Based Learning has successfully met the target goals, effectively boosting the Pancasila Education outcomes for Grade IV B students at SDN Pakis 1 Surabaya for the 2023/2024 academic year. The Problem-Based Learning model is characterized by fostering critical thinking skills among students, thereby facilitating the teaching process.